Vaccination coverage and immunization safety among children with special health status in Chongqing, China - Binyue Xu; Yi Zhang; Chao Zhou; Qing Wang; Rongsheng Luan (Taylor & Francis Group, 2022)
Vaccination of children with special health status has become one of the most urgent issues in China. We aim to evaluate vaccination coverage and safety as well as its associated factors among children with special health status in China during 2016‒2020. We conducted a retrospective cohort review of all children with special health status recorded in the Electronic Immunization Registries System in Chongqing, China, between 2016 and 2020. Univariate and multivariate logistic regression analyses were used to analyze the influence factors. Among the 2,175 children with special health status enrolled in the study, the overall vaccination coverage rate was lower than that among the general population, and the incidence of adverse event in them following immunization was very rare. Children with congenital heart disease were better vaccinated (aOR = 1.508-6.331), while most of the jaundice children had missed vaccination (aOR = 0.441‒0.556). The purchase of vaccine compensation insurance was associated with higher completion rate of basic immunization for Bacillus Calmette-G vaccine (aOR = 1.706, 95% CI: 1.249‒2.329) and rotavirus vaccine (aOR = 1.346, 95% CI: 1.061‒1.708). Children with special health status can be safely vaccinated. However, the vaccination coverage in these huge and vulnerable group is too low to protect them from vaccine-preventable diseases through immunization. More researches and interventions should be conducted to ensure a higher vaccination rate among the children with special health status.